The Islamization Process of the Population of the South of Western Siberia in the 13th–16th centuries - Maslyuzhenko D.N. (Золотоордынское обозрение, 2019)
Research objective: To identify the stages and consequences of the Islamization process of the population of the south of Western Siberia in the 13th–16th centuries. Research material: The research work was conducted on the basis of analysis of published sources: annals, chronicles, ambassadorial documents, missive letters and contracts, travellers’ notes, archaeological and ethnographical materials. Results and novelty of the research: Historiography of Siberian Islam traditionally considers Kuchum Khan as the central figure in the process of Islamization of local Turkic-Tatar groups. As a rule, previous attempts at establishing Islam there are considered rather superficially. The author of the article believes that it is inappropriate to take the first from the second when considering the process of Islamization and lacking an understanding of some of its consequences. The acquaintance of the population with Islam began in the pre-Mongol period due to the presence in this territory of Turkic nomads familiar with the culture of Central Asia. Purposeful attempts to establish this religion were connected with the activities of the descendants of Shiban ibn Jochi in the ulus of which the western lands of the region under consideration were included. They directly fit into the corresponding trends in the central lands of the ulus of Jochi, especially during the period of Uzbek Khan. The existence of the wintering camps of the Shibanids on the Syr Darya, where Islam had a traditionally strong position, was an important factor. Thus, there were two potential centers for the introduction of Islam into Siberian lands (the Volga region and Central Asia), which had an economic impact on the Shibanid domain. The consequences of the activities of Muslim preachers were ambiguous. On the one hand, there were clashes on religious grounds, but on the other, alternative faiths, in particular Buddhism, clearly retained their positions on the Siberian periphery. With the beginning of Shibanid statehood in the form of the Uzbek Khanate, as well as its heirs in the region – the Tyumen and Siberian Khanates – the dynasty began to purposefully support the Muslim community, something expressed in the vocabulary of the aristocracy, the presence of seyyids and hafizes at the khan’s court, hutba’s and sikka’s implementations during the enthronement of the rulers. Obviously, this indicates the great importance of this community in supporting the power of the khan. Indirect evidence suggests that by the end of the fifteenth century, Islam was accepted not only by representatives of the elite, but also by ordinary nomads. However, the crisis of the local statehood of the Shibanid dynasty at the beginning of the sixteenth century became a factor in the departure of the khans and their supporting nomadic groups to the Syr Darya and the Aral Sea region. This led to a significant decrease in the number of local Muslims and a break in cultural traditions. Moreover, after 1563, the new Siberian khans, Ahmad Giray and Kuchum, faced the problem of sowing Islam in the territory of Siberia along the Irtysh which had not previously been directly subordinate to the khanate. The result was a new stage of Islamization which at the same time affected precisely the new groups of the population subordinated to the khan’s power.